Effects of auriculasin on vascular endothelial growth factor (VEGF)-induced angiogenesis via regulation of VEGF receptor 2 signaling pathways in vitro and in vivo. (November 2018) - Cho, Hyun-Dong; Moon, Kwang-Deog; Park, Ki-Hun; Lee, Yong-Suk; Seo, Kwon-Il
Abstract: Angiogenesis plays an important role in various pathological conditions such as cancer via excessive delivery of oxygen and nutrients. Recent studies have demonstrated that understanding the molecular basis of natural agents in angiogenesis is critical for the development of promising cancer therapeutics. In this study, auriculasin, an active component from Flemingia philippinensis, was found to exert strong anti-angiogenesis activity. Treatment with auriculasin suppressed proliferation of human umbilical vein endothelial cells (HUVECs) by modulating expression of Bcl-2, Bcl-XL, and vascular endothelial growth factor (VEGF). Further, auriculasin inhibited VEGF-induced chemotactic migration, invasion, and capillary-like structure formation of endothelial cells. In addition, auriculasin abrogated VEGF-induced vascular network formation around rat aortic rings as well as blocked accumulation of hemoglobin, endothelial cells and VEGF in the Matrigel plug of C57BL/6 mice. The inhibitory effect of auriculasin on angiogenesis was well correlated with inhibition of VEGF receptor 2 (VEGFR2) activation as well as phosphorylation of intracellular downstream protein kinases of VEGFR2 containing Akt, mammalian target of rapamycin (mTOR), phosphoinositide 3-kinase (PI3K), p-38, extracellular signal-related kinase (ERK), and Src. Taken together, this study reports that auriculasin potently inhibits angiogenesis by modulating VEGFR2-related signaling pathways, which further validates its great potential in clinical applications. Graphical abstract: Highlights: Auriculasin inhibited VEGF-induced endothelial cell migration, invasion, and differentiation into capillary-like structure. Auriculasin inhibited AKT/mTOR signaling and MAPK pathways in HUVECs. Auriculasin inhibited activation of VEGFR2. Auriculasin suppressed VEGF-induced angiogenesis in vivo .